A aprendizagem de catálise enzimática por meio de casos: proposta para o ensino de química - Goulart, Thiago Pereira (Universidade Federal de São Carlos, 2018)
The fundamental aim of provoking innovative forms of knowledge construction in Chemistry during basic education requires the instrumentalization of strategies that can show re-significances of pedagogical practices and understandings about learning in Chemistry, as well as in the other Natural Sciences. Thus, the present study started from the foundations of the strategies of resolution of Investigative Cases and Reflexive Portfolios in order to propose a situation of learning from the enzymatic chemical reactions. The paper proposed the resolution of an Investigative Case written for the specific purpose of which Secondary School students of a private college, approaching a situation related to the daily life of a student of the same series. The writing of the case sought to value the construction of the empathy of the students who would solve it, as a way to dynamize the identification and construction of meanings by them regarding the problem situation presented in the case. The resolution steps were recorded in Reflective Portfolios, and from the totality of these reports produced the body of data used to analyze the reports was extracted. The work of orientations, discussion and resolution of cases involved individual and work steps and group discussions. The main objective of the present study is the characterization of ways in which the development of strategies that value the autonomy, the reflexive character and the identification of the learning objects within the daily life of the students can be possible. From the analysis of the results, four analytical categories emerged that characterize this strategy: the identification of the enzymatic reactions in the daily life of the character of the case; a progressively complex discussion about the structure of the substances and the chemical reactions in which they participate; the identification and discussion of the energy distribution characteristic in determining the occurrence of specific chemical reactions; and, finally, an analysis of the way in which critical judgments are made by the subjects of learning about the sources and the quality of the information they use to support their discourses. Based on the analyzes carried out, it is intended the formulation of a guide with guidelines for teachers and students on how to use investigative cases and reflexive Portfolios in their learning strategies, which concludes the study. One of the possibilities is to join the characteristics, data and discussions present in the Study, elements for an epistemological foundation regarding how it may be possible to raise knowledge in Chemistry from the two instruments presented in the Study - the Cases and the Portfolios - teaching practices that allow expanded views on knowledge, encompassing several areas and different forms of language. The study was carried out in a step-by-step manner, with each one of them orienting the teacher-researcher to the students' own demands. In this way, it was possible to describe learning paths and mechanisms from the forms of reports and reflection presented in the Reflective Portfolios.
The learning of enzymatic catalysis by cases: proposal for the teaching of chemistry
Keywords: Química; Catálise enzimática; Casos investigativos; Portfólios; Chemistry; Enzimatic catalysis; Investigative cases; CIENCIAS EXATAS E DA TERRA::QUIMICA